Retrospective Study on Anterolateral Mini-Thoracotomy in Emergency Surgical Drainage for Massive Pericardial Effusion Including Sternotomy Case - Wadud, Md Mohammad Armane; Imran, Md; Jahan, Israt; Khalilullah, Ibrahim; Kabir, Mohammod Humayun; Rahman, Mohammad Ahsan Habibur; Ghafoor, Nusrat; Hasan, Sharif; Siraj, Masoom (Bangladesh Heart Journal, 2024)
Background: The conventional method for managing the surgical drainage of an acute massive pericardial effusion typically involves a median sternotomy. Nevertheless, advancements in surgical optics and tools have enabled the utilization of progressively smaller incisions, such as a left anterolateral thoracotomy, for the same purpose. Aim of the Study: This study aimed to assess the surgical outcomes of left anterolateral mini-thoracotomy compared to median sternotomy for draining acute massive pericardial effusion. Methods: This research took place in the Cardiac Surgery Department at Ibrahim Cardiac and Research Institute, following approval from the local ethics committee, from June 2021 to June 2023. Fourteen patients with acute massive pericardial effusion necessitating emergency surgical drainage were included. The investigation concentrated on evaluating operative and short-term postoperative results to gauge the influence of two surgical drainage methods on patients' quality of life. Result: Both groups exhibited similar age, preoperative comorbidities, and ejection fraction. The sternotomy group required more operation time than the left anterolateral mini-thoracotomy group. Furthermore, the sternotomy group had a prolonged stay in the intensive care unit and hospital compared to the left anterolateral mini-thoracotomy group. Similar rates were observed for blood transfusion and chest tube drainage. However, two cases of superficial wound infection occurred in the sternotomy group. In the anterolateral thoracotomy group, no patients required conversion to full sternotomy, and all patients were alive at the one-month follow-up after hospital discharge. Conclusion: Employing a left anterolateral mini-thoracotomy for draining acute massive pericardial effusion was deemed a secure and reliable alternative to the traditional median sternotomy incision. Despite its limited operating field, requiring proficiency, this approach preserved sternal integrity, offered a more aesthetically pleasing incision, reduced the risk of wound infection, and decreased the need for analgesia. Additionally, it was associated with a faster recovery process and a shorter stay in the intensive care unit (ICU). (Bangladesh Heart Journal 2024; 39(2): 161-167